Pengembangan Manajemen Pariwisata Halal Berbasis Kearifan Lokal Sipakatau’, Sipakainge’, Sipakalebbi’ - Andi Zulfikar Darussalam; Syarifuddin Syarifuddin; Ega Rusanti; A. Darussalam Tajang (ITB AAS INDONESIA Surakarta, 2021)
Halal Tourism is one of the cultural-based tourist forms that Putting Islamic values and norms first. The potential for Halal Tourism development in Indonesia is enormous but needs to be upgraded in terms of the developer concept by applying lokal cultural values. One tourist destination in South Sulawesi is 'Taman prasejarah Leang-Leang' in Maros regency that has become a promising region To be developed as a Halal Tourism area by promoting lokal Sipakainge’ and Sipakalebbi’ concepts of wisdom. This study is a qualitative descriptive study using primary and secondary data sources through observation and documentation carried out by researchers. Research results are obtained if Sipakainge’ and Sipakalebbi’ can apply as Tourism clean development concepts by upholding the value of humanizing one another, reminding and respecting one another in the process. Additionally, the development can also be achieved by increasing the tools and infrastructure that makeup residence and characteristics of Halal Tourism.